Development and Validation of a Behavior Indicators Scale of Giftedness for Students with Autism Disorder - Wadaani, Majed; Abualfotoh, Muhammad (Jordan Journal of Educational Sciences, 2019)
Giftedness is the vital human capital in our world today, and communities are keen to ensure early identification of its indicators, in order to provide the necessary care for development and investment. As shortage in such studies exists, this study aimed to develop and validate a scale of behavioral characteristics for indicators of giftedness in students with autism disorder in the age range of (7-12) years. The procedures for this aim included several methods to verify the validity and reliability of the scale. A three-dimensional scale in its final form was released in this study: Metacognitive skills, visual-motor skills, and psycho-social skills; with total of (66) items of behavior that can be represented as indicators of giftedness that requires more nurturing services to get clarified and reflect in high performance.